FINANCIAL ACCESSIBILITY IN COST-SHARING POLICIES IN HIGHER EDUCATION IN MOZAMBIQUE - Joaquim, José Amilton; Cerdeira, Luísa (International Journal of Research -GRANTHAALAYAH, 2020)
The massive growth of the student population in higher education institutions has challenged traditional forms of public funding, and cost-sharing policies have been one of the options used by governments. In this sharing, it is important that, depending on the social and economic characteristics of students, issues related to equity and accessibility are safeguarded. This study seeks to understand how cost-sharing policies – taking into account the direct costs of attending higher education, indirect costs, other living expenses and the Mozambicans’ social and economic features – can help or hamper the access to higher education in Mozambique. The selected empirical research contexts encompass eight higher education institutions in the province of Gaza – universities and polytechnics – from the public and private sectors. Empirical data were collected from a questionnaire implemented with higher education students; furthermore, the authors carried out a document analysis on the financing of higher education in Mozambique and worldwide. Allows concluding that, in Mozambique, the cost-sharing model follows a dual-track policy. Also, the part of the financing still ensured by the State is far from meeting the real needs of students and families, due to the high study and living costs, which are well above the students/families’ income. There is no diversification of social support for students, and the only help students have comes from scholarships, whose allocation process is inefficient. This calls into question the issues of higher education equity and accessibility, especially for families with the lowest socio-economic conditions in the country.